Biochemistry and genetics - Ingram-Smith, Cheryl; Smith, Kerry S. (New York : McGraw-Hill, 2005)
"This one-of-a-kind test prep guide helps you: get to know material on course exams and the USMLE step 1, practice with 500 clinically-oriented multiple-choice questions, review key facts for exam success, and build confidence, skills, and knowledge."--BOOK JACKET.
Rev. ed. of: PreTest biochemistry and genetics. 1st ed. 2001.
Keywords: Biochemistry -- Examinations, questions, etc; Genetics -- Examinations, questions, etc; Biochemistry -- Examination Questions; Genetics, Medical -- Examination Questions